Spectroscopic characterization of lithium thiophosphates by XPS and XAS – a model to help monitor interfacial reactions in all-solid-state batteries. Issue 30 (19th July 2018) - Dietrich, Christian; Koerver, Raimund; Gaultois, Michael W.; Kieslich, Gregor; Cibin, Giannantonio; Janek, Jürgen; Zeier, Wolfgang G.
Abstract : Shift of binding energies upon depolymerization of superionic lithium thiophosphates. Abstract : Inspired by reports of redox active interphases in all-solid-state batteries employing fast conducting lithium thiophosphate solid-state electrolytes, we investigated the compositional depolymerization of interconnected PS4 tetrahedra in (Li2 S) x (P2 S5 )100− x glasses (50 < x < 80) by X-ray absorption spectroscopy (XAS) and X-ray photoelectron spectroscopy (XPS). Based on the observed energy shifts with composition, we present a structural model of the three different bonding types describing the structures of either crystalline or amorphous thiophosphates. This model and reference data characterizes amorphous thiophosphates based on their inter-tetrahedral connectivity and helps to distinguish malign decomposition reactions from reversible redox reactions at the cathode active material/solid-state electrolyte interface. This work highlights the importance of a combined analytical approach and appropriate reference compounds to elucidate the interface reactions in all-solid-state battery systems.